Epidemiological study of ulcerative proctocolitis in Indian migrants and the indigenous population of Leicestershire. Issue 5 (May 1992) - Probert, C S; Jayanthi, V; Pinder, D; Wicks, A C; Mayberry, J F
Abstract : A retrospective epidemiological study of ulcerative colitis (UC) and proctitis was performed in Leicestershire from 1972-89. Potential cases were identified from hospital departments of pathology, endoscopy, and medical records and from general practitioners. The county population includes more than 93, 000 South Asians. There were 573 cases of UC and 286 of proctitis in Europeans and 115 cases of UC and 29 of proctitis in South Asians. The standardised incidence of UC in Europeans and South Asians was stable, except in Sikhs in whom it had increased rapidly. The relative risk of UC to South Asians was 2.45. The standardised incidences of UC in South Asians during the 1980s were: 10.8/10(5)/year in Hindus (95% confidence interval (CI) 7.4-14.1 cases/10(5)/year) 16.5/10(5)/year in Sikhs (95% CI 7.9-25.2 cases/10(5)/year), and 6.2/10(5)/year in Muslims (95% CI 1.6-10.9 cases/10(5)/year). There was no difference in incidence between Asians from East Africa and India. The standardised incidence of UC in Europeans was 5.3/10(5)/year (95% CI 4.3-6.3 cases/10(5)/year). The standardised incidences of proctitis were 3.1/10(5)/year (95% CI 1.9-2.5 cases/10(5)/year) in South Asians and 2.3/10(5)/year (95% CI 1.8-2.4 cases/10(5)/year) in Europeans. Ethnic groups had a similar disease distribution, except Sikhs in whom it was less extensive. Despite the similar disease distribution, South Asians had fewer operations and complications from UC than Europeans. There was a bimodal age specific incidence in Europeans, but not in other ethnic groups. First and second generation South Asians were at similar risk. Hindus and Sikhs have a significantly higher incidence of UC than Europeans in Leicestershire.